Influence of the nature of the methyling agent and solvent on the directions of the methylation reaction of 2-methylqinazolin-4-ones (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
It is known that methylation of pyrimidine and quinazoline derivatives proceeds in different directions with the formation of one or two isomers. So, if 2-methilquinazolin-4-one is methylated at the N-1 and N-3 atom or simultaneously at these two centers, then methylation of 2-methyilquinazolin-4-one occurs mainly at the “softer” reaction center